Demographic Differences in Emotional Impact of COVID-19 Pandemic and Country Lockdown: A Cross-sectional Survey of Household Members in Ebonyi State, Nigeria - Ngwakwe, Patricia Chinma; Anugwo, Margret Ndidiamaka; Elom, Nwamaka Agbe; Ogbu, James Ekuma; Ojide, Rita Ngozika; Alegu, Deborah Nnebuife; Ogah, Christian Ikechukwu; Nwimo, Ignatius Obilor (Archives of Business Research, 2024)
COVID-19 pandemic and country lockdown could negatively impact on the emotions of several household members. Using cross-sectional the study investigated demographic differences on emotional impact of COVID-19 pandemic and country lockdown of 392 household members. The instrument (α = 0.73) used for data collection was a 15-item structured emotional impact of COVID-19 lockdown questionnaire (IMC-19LQ). Data collected were analyzed using means, standard deviations, ANOVA and t-tests. Results showed all age groups suffered high emotional impact of COVID-19 pandemic and country lockdown; participants of all levels of education suffered high emotional impact of the lockdown. Farmers and artisans suffered higher impact of the pandemic lockdown than others. Both married and singles reported high emotional impact of the lockdown. ANOVA and t-test revealed no significant differences in the emotional impact of the lockdown among participants in relation to age, level of education and marital status (p > 0.05) but a significant difference existed in relation to occupation (p < 0.05). Collaboration of health educators, social and clinical psychologists through seminars and workshops may be used to achieve promotion of psychological wellbeing of household members.